(3eQTO GdRhGQ Edi bHhQ GdCHQGQs - (3GdTGQYj , YHO GdQMef Hf ecj Hf YKeGf Hf CHj GdNQe, ehab GdOjf CHh eMeO,J (B780 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi TQa LHd GdebWe Hcd eSLO s
(3PcQ ajg LHd GdebWe hChOjJg hbHhQ GdUGMdjf GdJiai SaMgs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B339s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B34 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B245 s
Keywords: (3GdJGQjNs